Effects of microplastics contamination on marine biota - Santana, Marina Ferreira Mourão (2015)
Microplastic pollution (particles < 5mm) is one of the most widespread impacts from modern society. Here, microplastic impacts were investigated through experimental assessments considering different exposure scenarios using mussels and micro-PVC as models. These aimed to investigate mussels\' physiological signs of stress under acute and chronic exposures and microplastics transference, assimilation and retention along food chains. In acute exposures, PVC intake affected mussels\' physiology over time, also influenced by plastics additives and particle concentration. Interactions among exposure factors (time, presence of additives and concentration) were more relevant than their individual effect, indicating the singularity of each contamination scenario. Long-term contact did not affect mussels, indicating the influence of time to acclimation. Microplastics were not assimilated and retained along food chains, but only biotransferred from prey tissues to predators\' tract, showing the influence of prey contamination on the effectiveness of microplastics biotransference. To evaluate risks in nature, microplastic ingestion was investigated in mussels from the Santos Estuary. Santos Estuary contained microplastics in 75% of sampled mussels, an issue of environmental and human concern. This study illustrated that microplastics impacts on mussels vary with microplastics characteristics, exposure scenario and species vulnerability, highlighting the need for more toxicological and risk evaluation studies.